DATA MINING ALGORITMA APRIORI MENENTUKAN PEMBELIAN MATERIAL KONSTRUKSI BANGUNAN - Simanjuntak, Pastima; Handoko, Koko; Elisa, Erlin; Suharyanto, Cosmas Eko (Jurnal Teknik Informatika UNIKA Santo Thomas, 2023)
In Indonesia, several different types of construction materials are extensively utilized, particularly for houses or structures and other infrastructure sectors. Building materials might be constructed of metal/iron, wood, concrete, or reinforced concrete. Houses, buildings, or all facilities, equipment, or infrastructure such as bridges, road construction, and telecommunications facilities are commonly referred to as structures. Material is extremely significant in deciding project costs. Due to a lack of effective planning and control during the construction implementation stage, the usage of materials in the field frequently results in huge volumes of material remaining, hence measures to limit material waste are critical to implement. The goal of this research is to choose building materials. This study uses a data mining technique with an a priori algorithm and the results of this study can be utilized to see consumer selection patterns to boost product sales, as well as the subsequent decisions to enhance product sales, as well as see the resulting decision to assist in the selection of building construction materials in the City of Batam.